The Impact of Diffusion of Innovation on Classroom Management - Ghufron, M. A.; Mardiana, Harisa (KnE Social Sciences, 2023)
The integration of digital technology in the school environment has led to transformative changes in classroom management, affecting both teachers and students. Teachers play a central role in this process, and research on classroom management innovations highlights various variables that influence learning outcomes. Consequently, schools must grasp the implications of adopting these innovative practices. This study employs a qualitative approach, focusing on in-depth exploration of specific scenarios related to the use of digital technology in classroom management. Interviews were conducted with school administrators, including principals, teachers, and students from secondary schools. The findings indicate that the post-COVID-19 learning environment, with the widespread use of digital technology, has significantly impacted students. The incorporation of digital tools has empowered students to manage their time effectively and actively participate in class activities. Teachers, on the other hand, have embraced digital technology for online classes and blended learning approaches, thereby enhancing students’ understanding and engagement in learning. Additionally, the evaluation processes implemented by schools have facilitated the establishment of effective learning models, resulting in the successful diffusion of innovation in classroom management. Future research could further enhance the curriculum and education system by exploring additional opportunities for utilizing digital technology in education. Keywords: diffusion of innovation, digital technology, management class 1